2020
DOI: 10.1115/1.4048336
|View full text |Cite
|
Sign up to set email alerts
|

Global Sensitivity Analysis for Patient-Specific Aortic Simulations: The Role of Geometry, Boundary Condition and Large Eddy Simulation Modeling Parameters

Abstract: Uncertainties affect the reliability of the numerical simulation of hemodynamics in patient-specific settings and rigorous Uncertainty Quantification (UQ) is in order. This work presents a UQ study on the aorta flow, for assessing the sensitivity of the clinical relevant quantities to the morphology and imprecise knowledge of the inflow boundary condition using the Polynomial Chaos Expansion based Sobol' indices. The geometrical uncertainty is modeled based on a set of longitudinal imaging data of a patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…TL pressure dominates FL pressure up to the first re-entry tear, where FL pressure begins to dominate. This trend is observed in other computational studies 43 . FL pressurisation is not directly correlated with FL growth in this patient, with growing regions all showing different TMP characteristics; TMP is strongly positive near α , near-zero at β and negative from γ onward.…”
Section: Resultssupporting
confidence: 88%
“…TL pressure dominates FL pressure up to the first re-entry tear, where FL pressure begins to dominate. This trend is observed in other computational studies 43 . FL pressurisation is not directly correlated with FL growth in this patient, with growing regions all showing different TMP characteristics; TMP is strongly positive near α , near-zero at β and negative from γ onward.…”
Section: Resultssupporting
confidence: 88%
“…It uses a stochastic approach to obtain continuous response surfaces of the hemodynamic parameters starting from a few deterministic simulations and is computationally more efficient than a Monte Carlo approach. Furthermore, using the method of polynomial chaos expansion for a global sensitivity analysis, it has been found that the sensitivity to geometry may be different during different instants of the heartbeat and in different vascular regions ( Xu et al, 2021 ).…”
Section: Verification Validation and Uncertainty Quantificationmentioning
confidence: 99%
“…Considering the computational expensive CFD strategies used for computing phaseaveraged solutions within this thesis (including the large amount of manual labor in both preand post-processing steps), the future focus should be on identifying cost reductions towards the most effective or "bang for the buck" solution strategies. In a newly published study [258], a variance-based sensitivity method was utilized to attribute the uncertainty of the outputs to specific modeling inputs, which required significantly less number of samples than standard UQ methods. This UQ framework used LES on patient-specific aortic aneurysm models and an idealized aortic arc benchmark to assess the output sensitivity to uncertainties in geometry and inflow variations, and modeled subgrid dissipation strength.…”
Section: Chapter 6 Outlookmentioning
confidence: 99%